Implementation of IoT Gateway based Raspberry Pi 3 B+ in Lora 433 Mhz Communication System on Flood Detection - Hana Graceila Sitindjak; Yuliarman Saragih; Reni Rahmadewi (VOLT : Jurnal Ilmiah Pendidikan Teknik Elektro, 2022)
Frequent floods in Indonesia cause many problems, therefore it is necessary to create devices with the implementation of Raspberry Pi-based IoT Gateways in the LoRa communication system. The gateway has a function as a performance informer and makes it easy to access the exchange of information data and the space to store a lot of data received from the node. To maximize the implementation, a Gateway was designed consisting of Raspberry Pi 3 B+, ESP-32, and LoRa 433 MHz. This research uses the Research and Development method. The data obtained includes how the Gateway works which will be displayed on the Raspberry Pi screen properly, monitoring the state of the water using Thinger io. Data were obtained from the Gateway and data transmission system from Gateway to Client as much as 42 times with an RSSI value of -53.3 dBm in very good condition at a distance of 1.54 km with a wajanbolic antenna and a very poor RSSI of -91.4 dBm at a distance of 8.32 km without a wajanbolic antenna. A poor RSSI value can cause an error. The results obtained from the experiments in the study showed that the implementation of Raspberry Pi-based IoT Gateways in the LoRa communication system on flood detection worked well.